Diabetes: awareness and management. Data of Passi and Passi d'Argento surveillance in Lazio, Italy. (30th September 2020) - Paradiso, F; Agosti, G; Prencipe, G P; Trinito, M O; Iacovacci, S; Contoli, B; Minardi, V; Masocco, M
Abstract: Background: Diabetes is a health emergency: in Italy over 3 million people are diabetics. In Lazio region a high percentage of population is affected by diabetes. Data are collected from two Italian population surveillance systems, Passi during 2015-18 and Passi d'Argento (PdA) during 2016-2018; this trasversal study was conducted to investigate diabetes awareness and clinical management in Lazio. Methods: Passi and PdA collect representative data providing a telephone interview with a standardized questionnaire to a representing sample (18-69 and over 65 aged respectively), randomly selected and sex-and-age stratified. In both questionnaires a diabetes section assesses diagnosis, knowledge of HbA1c, health setting and number of annual checks. Data refer to whom affirm to be diagnosed with diabetes. Results are shown by prevalence and 95% CI. Results: Diabetes prevalence grows with age, it does not reach 1% in people under 50 years, it is 9% for the age group 50-69 years and 20% in over 75. Serious economic difficulties and low education level are related to higher prevalence. Among diabetics, 18.7% (15.42-22.46) from Passi and 24.2% (20.29- 28.61) from PdA ignore HbA1c. About clinical management, 1.5% (0.73-2.90) in Passi do not receive any care from doctor; the whole sample of PdA receives medical care. Most of the respondents in both surveillance are managed by diabetes care team (43.76% in Passi - 39.87% in PdA), reporting to receive care about three times a year on average. No significant differences are observed between economic and education levels. Conclusions: High percentage of diabetics, not knowing HbA1c, are not aware about disease. Patient empowerment is necessary to gain control over disease and increases capacity to act on it. Health education should be improved and diagnostic and therapeutic pathways, recently introduced in Lazio Region, should be better structured. Population surveillances allow to plan and evaluate programs and interventions. Key messages: Fight the lack of awareness with patient empowerment to gain control over diabetes. Population surveillances are valuable tools to plan and evaluate programs and interventions in Public Health.